Latin America, on the frontiers of art - Ciciani Mondino, Fiorella Sofía (Millcayac - Revista Digital de Ciencias Sociales, 2025)
Formulating a definition of Latin American art often involves distinguishing it from "Art," which seems to encompass only what is produced in Europe. A possible answer to what Latin American art is can be found in its relationship with the social sphere, with history, and with the search for an original identity in tension with both European and local traditions. A paradigm shift would be to think about art from this perspective, highlighting the extraordinary variety of symbolic production on the continent, overcoming the colonial mark, embracing the present mixtures, and thus crossing and erasing (or not) the boundary of what we believe we should call Art.